Extinction of West Nile Virus by Favipiravir through Lethal Mutagenesis - Escribano-Romero, Estela (Antimicrob Agents Chemother, 2017)
Favipiravir is an antiviral agent effective against several RNA viruses. The drug has been shown to protect mice against experimental infection with a lethal dose of West Nile virus (WNV), a mosquito-borne flavivirus responsible for outbreaks of meningitis and encephalitis for which no antiviral therapy has been licensed; however, the mechanism of action of the drug is still not well understood. Here, we describe the potent in vitro antiviral activity of favipiravir against WNV, showing that it decreases virus-specific infectivity and drives the virus to extinction. Two passages of WNV in the presence of 1 mM favipiravir—a concentration that is more than 10-fold lower than its 50% cytotoxic concentration (CC(50))—resulted in a significant increase in mutation frequency in the mutant spectrum and in a bias toward A→G and G→A transitions relative to the population passaged in the absence of the drug. These data, together with the fact that the drug is already licensed in Japan against influenza virus and in a clinical trial against Ebola virus, point to favipiravir as a promising antiviral agent to fight medically relevant flaviviral infections, such as that caused by WNV.